Gynaecology (Elsevier science, 2003)
This comprehensive, up-to-date, and readable text covers all aspects of gynecology, including reproductive endocrinology, gynecological oncology, and urogynecology, with an emphasis on clinical management throughout. Its five principal sections examine basic principles and investigations, reproductive medicine, benign and malignant tumours, urogynecological disorders, and women's reproductive health. Extensive coverage of the entire specialty Fully illustrated and referenced Contributions from gynecologists worldwide Features excellent coverage of STDs, PID, and urinary tract infection Presents new material on molecular biology adolescent gynecology evidence-based care and risk management strategies. Addresses the importance of outpatient surgery. Examines general surgical procedures performed by gynecologists. Offers stronger surgical coverage enhanced by new illustrations.